Cellular Heterogeneity of Mesenchymal Stem/Stromal Cells in the Bone Marrow - Mabuchi, Yo; Okawara, Chikako; Méndez-Ferrer, Simón; Akazawa, Chihiro (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem/stromal cells (MSCs) are present in various body tissues and help in maintaining homeostasis. The stemness of MSCs has been evaluated in vitro. In addition, analyses of cell surface antigens and gene expression patterns have shown that MSCs comprise a heterogeneous population, and the diverse and complex nature of MSCs makes it difficult to identify the specific roles in diseases. There is a lack of understanding regarding the classification of MSC properties. In this review, we explore the characteristics of heterogeneous MSC populations based on their markers and gene expression profiles. We integrated the contents of previously reported single-cell analysis data to better understand the properties of mesenchymal cell populations. In addition, the cell populations involved in the development of myeloproliferative neoplasms are outlined. Owing to the diversity of terms used to describe MSCs, we used the text mining technology to extract topics from MSC research articles. Recent advances in technology could improve our understanding of the diversity of MSCs and help us evaluate cell populations.